ANALOG SIMULATION PROBLEMS NONSTATIONARY GAS DYNAMICS - A. A. Kukin; V. V. Trofimov; O. A. Eycfeld (Научный вестник МГТУ ГА, 2016)
In this paper the possibility of using hydraulic analog simulation in the study of problems of unsteady gas dynamics is considered. The analysis of differential equations of unsteady motion of bodies in supersonic flow using the theory of similarity and dimensional analysis. Obtained similarity criteria that must be identical for both the real gas flow and the modeling of fluid flow. Using a hydraulic analog modeling for research in non-stationary gas dynamics provides valuable information necessary for understanding the physics of the processes and the construction of more sophisticated mathematical models.